Characterization, antibacterial and in vitro compatibility of zinc-silver doped hydroxyapatite nanoparticles prepared through microwave synthesis - Iqbal, N.; Kadir, M.R.A.; Mahmood, N.H.; Salim, N.; Froemming, G.R.A.; Balaji, H.R.; Kamarul, Tunku (2014)
We investigated the possibility of enhancing hydroxyapatite (HA) bioactivity by co-substituting it with zinc and silver. Zn-Ag-HA nanoparticles were synthesized by using the microwave-assisted wet precipitation process, and their phase purity, elemental composition, morphology, and particle size were analyzed by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDX). FTIR, XRD, and EDX results showed the characteristic peaks of the Zn-Ag-HA structure, while SEM results demonstrated that the nanoparticles were of spherical shape with a particle size of 70-102 nm. Antibacterial tests of the nanoparticles revealed their antibacterial activity against Staphylococcus aureus and Escherichia colt. By using simulated body fluid (SBF), an apatite layer formation was observed at 28 days. In vitro cell adhesion assay confirmed the cell attachment of normal human osteoblast (NHOst) cells to the disc surface. MTT (3(4, 5-dimethylthiazol-2-y1)-2, 5 diphenyhetrazolium bromide assay indicated that the cells were viable, and the cells proliferated faster on the disks than on the control surface due to the presence of metal ions. In conclusion, the novel Zn-Ag-HA nanoparticles were found to be compatible with in vitro experiments and having potential antibacterial properties. Therefore these nanoparticles could be a promising candidate for future biomedical applications. (C) 2013 Elsevier Ltd and Techna Group S.r.l. All rights reserved.